Regulation of norrin receptor frizzled-4 by Wnt2 in colon-derived cells - Planutis, Kestutis (BioMed Central, 2007)
BACKGROUND: Norrin is a potent Wnt pathway ligand. Aberrant activation of this signaling pathway can result in colon tumors but the role of norrin-based signaling in the genesis of colon cancer, and its relationship to activation of the pathway by traditional Wnt ligands, is not defined. RESULTS: Fresh normal human colon tissue and all the cell lines studied expressed mRNA for Fz4, LRP5 and norrin, except Colo205 which lacked Fz4 expression. Canonical Wnt pathway throughput was increased slightly in NCM460 following treatment with Wnt3a CM but was inhibited by Wnt2 and Wnt1. The colon cancer cell line, RKO, responded to Wnt3a CM, Wnt2 and Wnt1 by increasing canonical Wnt pathway throughput. Wnt5a did not affect Wnt pathway throughput in either cell line. Wnt2, but not Wnt3a, abrogated Fz4 expression in NCM460, but not in RKO or another colon cancer cell line, HCT116. This effect on Fz4 was confirmed at both the RNA and protein levels via RT-PCR and a norrin binding assay. The expression of all others 9 Fz receptors did not change after treatment of NCM460 cells with Wnt2. CONCLUSION: The data suggests that colonic mucosa and colon tumors may possess two autoregulatory positive Wnt feedback loops, one through canonical signals induced by Wnt:Fz interactions and one through signals resulting from norrin:Fz4 interactions. The latter interactions may be modulated via regulation of Fz4 expression by Wnt2. Retention of Fz4 by cancers, in contrast to the loss of Fz4 by normal mucosal cells, could provide a selective advantage to the tumor cells. Fz4 expression may play a critical role in responses to Wnt signaling in the tumor microenvironment.